Effect of coenzyme Q10 on mitochondrial respiratory proteins in trigeminal neuralgia - Chutikorn Khuankaew (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. Trigeminal neuralgia (TN) is the neuropathic pain. Mitochondrial dysfunction, increased oxidative stress, and inflammation demonstrated in chronic pain. Carbamazepine (CBZ) is the first-line drug for TN, however, it is still insufficient. Coenzyme Q10 (CoQ10) has been used as the additional supplement for pain therapy. Nonetheless, mitochondrial respiratory proteins, oxidative stress, and inflammation in TN, and the add-on effects of CoQ10 on those defects have never been investigated. CBZ-treated TN-patients, naïve TN-patients, and control subjects were included. CBZ-treated TN-patients were randomised into two subgroups, received either CoQ10 or placebo for 2 months. Pain levels were evaluated, and peripheral blood mononuclear cells were isolated to determine the oxidative stress, mitochondrial oxidative phosphorylation (OXPHOS), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), and cytokines including TNF-α, IL-1β and IL-18 mRNA expression. Pain scales, oxidative stress, and OXPHOS levels were greater in naïve TN-patients than control, whereas the cytokine profiles were unchanged. Although pain scales were lower in CBZ-treated TN-patients than in naïve TN-patients, oxidative stress, OXPHOS, and cytokine expression profiles were not different. PGC-1α levels found to be increased in CBZ-treated TN patients when compared with the naïve group. CoQ10 supplement in CBZ-treated TN patients reduced pain scale and oxidative stress and increased antioxidants levels when compared with placebo group. However, OXPHOS, PGC-1α, and cytokines were not different between groups. These findings suggest that increased oxidative stress could be potentially involved in the pathogenesis of TN. CoQ10 supplements can reduce oxidative stress, leading to more effective pain reduction in TN patients being treated with CBZ.